ABOUT THE PROBLEM OF STUDYING THE AWARENESS OF TEACHERS, STUDENTS AND UNDERGRADUATES IN THE ISSUES UNDER CONSIDERATION (EDUCATION IN THE 21ST CENTURY, 2023)
The present article reveals the possibility of studying the awareness of teachers of varioustypes of schools (special, integrated, mass), students and undergraduates of pedagogicaluniversities (future teachers) in the issues under consideration, particularly, related to theformation and development of geometric conceptions and definitions in children with visualimpairments. The success of this study depends on the level of awareness of teachers of mentionedschools, students and undergraduates of pedagogical universities about the peculiarities of thedevelopment of those children, the means, methods and conditions for their application to addressthese issues.It is known, that visual impairment significantly complicates the playing, physical, cognitive,educational, labor and other types of activities of those children.Blind and visually impaired students are characterized by passivity, introversion, insufficientactivity. Therefore, the study of many aspects of the considered problem and the development ofapproaches to the development of the level of awareness of teachers, students and undergraduatesof pedagogical universities in the issues under consideration, particularly, related to the formationand development of geometric ideas and concepts in children with visual impairments and thedevelopment of approaches to expanding the level of awareness in these issues will serve as thebasis for improving the formulation of this work in the types of schools under consideration.In the special scientific and methodological literature, the importance of studying thisproblem is emphasized; however, it is insufficiently developed in theoretical and practical aspectsthat in its turn defines the relevance of this study, its theoretical and practical significance.
Keywords: blind, visually impaired, children with visual impairments, Tel, students, undergraduates, geometric representations and concepts, formation development and development, sociological survey